Charged Vector Boson (W ±) production in simulated proton-proton collisions at √s = 5.36 TeV. - Potgieter, Jakobus (Department of Physics, 2026)
In this work, the focus is on the charged vector boson (W ±) production in the forward rapidity region of simulated relativistic proton-proton collisions, where the POWHEG and Pythia Monte Carlo (MC) event generators are used to simulate the events of interest for the analysis. The W ± boson production is studied via the muonic decay channel as W ± → μ±+νμ (–). It is theoretically motivated in the work that this process can serve as a probe of the initial state of the collision, since the W ± boson is produced in the hardest partonic interaction and neither the W ± boson nor the μ± have a colour charge. The muonic decay of heavy-flavour (HF) mesons in the same forward rapidity region is also investigated, where it is shown that these processes serve as the dominant background for the muon production from W ± boson decays. The primary charged-particle multiplicity is also introduced as an observable of interest, where the self-normalised W ± boson production as a function of the normalised multiplicity is defined and studied specifically. For this observable, it is shown that a linear trend is obtained when estimating the multiplicity in the central rapidity region and using the default Monash Tune. The choice of the central region for the multiplicity estimation is clearly motivated by looking at auto-correlation effects - which are shown to effect the slope of the multiplicity observable. In addition, it is shown that the slope of the multiplicity observable is also sensitive to the multi-parton interaction (MPI) and colour reconnection (CR) models - which motivates the use of the observable to probe the initial-state of the collision. Finally, a feasibility study is also performed to investigate whether the same study can be done with the ALICE Run 3 proton-proton reference data at the same centre-of-mass energy - where an estimation of the available statistics for the W ± → μ±+νμ (–) process is presented. Through the work, it is also argued that the study in proton-proton collisions can serve as a meaningful baseline measurements for other collision systems - such as proton-lead and lead-lead.